Acrylamide induces locomotor defects and degeneration of dopamine neurons in Caenorhabditis elegans. Issue 1 (15th April 2015) - Li, Jia; Li, Dan; Yang, Yongsheng; Xu, Tiantian; Li, Ping; He, Defu
Abstract: Acrylamide can form in foods during the cooking process and cause multiple adverse effects. However, the neurotoxicity and mechanisms of acrylamide have not been fully elucidated. In Caenorhabditis elegans, we showed that 48 h exposure to 10–625 mg l −1 acrylamide resulted in a significant decline in locomotor frequency of body bending, head thrashing and pharynx pumping. In addition, acrylamide exposure reduced crawling speeds and changed angles of body bending. It indicates that acrylamide induces locomotor defects, along with parkinsonian‐like movement impairment, including bradykinesia and hypokinesia. Acrylamide also affected chemotaxis plasticity and reduced learning ability. Using transgenic nematodes, we found that acrylamide induced downexpression of P dat‐1 and led to the degeneration of dopaminergic neurons. Moreover, the enhanced expression of unc‐54, encoding a subunit of α‐synuclein was found. It illustrates that acrylamide is efficient in inducing crucial parkinsonian pathology, including dopaminergic damage and α‐synuclein aggregation. These findings suggest the acrylamide‐induced locomotor defects and neurotoxicity are associated with Parkinson's disease. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In Caenorhabditis elegans, we showed that 48 h exposure to 10‐625 mgl −1 acrylamide resulted in significant declines in locomotor behavior and decrease of crawling speeds and body bending angles, which indicated locomotor defects, along with Parkinsonian‐like impairment. Acrylamide also affected chemotaxis plasticity and reduced learning ability. Moreover, acrylamide induced down‐expression of Pdat‐1 and enhanced expression of unc‐54, which indicated degeneration of dopaminergic neurons and aggregation of α‐synuclein. It suggests that the neurotoxicity of acrylamide is associated with Parkinson's disease.